Studies on Accumulation of Mn2+ by Nasturtium officinale in Water by Biosorption - Opak-Kara, Yesim; Basaran, Davut; Isikalan, Cigdem (Asian Journal of Chemistry, 2010)
In present study, Nasturtium officinale has been used as a plant. The plant has been collected from the campus of Dicle university. The study has been achieved in vitro. Air roots of the plant with the same number and morphology of leaf has been chosen. For biosorption of Mn2+ metal ions by Nasturtium officinale, the solutions were prepared as 0.1; 0.3; 0.5; 1; 2; 3; 4 and 5 ppm, respectively. Water samples has been prepared from 1000 ppm stock and put them to balon joje. After this process, the plants have been transferred to the erlens and wait for 24, 48 and 72 h. The erlens have been tightly closed with parafilm. The general appearence of the plants have been observed at the beginning and after 24 h. The plants has been analyzed with atomic absorption spectrometry by receiving 2 mL of water samples for calculation of concentration. The A and B values have been found by drawing the calibration lines in UV. The wet weight has been measured with sensitive balance. The quantity of Mn2+ absorption of plants has been calculated with the dependence of the wet weight.